Employee Performance Improvement Through Workplace Design - Kapraja Sangadji; Lorimase Sangadji (Peneliti.net, 2019)
Every organization has an obligation to design, organize and improve workplaces, which enables employees to carry out their duties and functions optimally so as to improve superior performance. Pleasant workplace design plays an important role in improving effectiveness and efficiency of performance. With the optimal workplace design, it can grow the motivation for employee and to facilitate the use of productivity in improving performance and productivity. Conversely, workplaces that are not well designed will potentially lead to a decrease in employee performance and productivity. Standards for improving employee performance through workplace structuring design are (1) optimal results, (2) efficiency, (3) satisfaction, and (4) adaptability. The workplace design organization basically refers to 4 principles, namely (1) short distance principles, (2) the principle of all use of space, (3) the principle of the arrangement of workplaces and (4) the principle of the form of work. Through workplace design both are expected to improve the performance and production of employees as an organization.